Chronic glomerulonephritis of the mixed type in patient with HBV-infection (Clinical case) - V. S. Adonyeva; A. B. Botchkarev; O. S. Saurina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. To present a clinical case of the chronic glomerulonephritis (CGN) associated with hepatitis B virus (НВV) infection. To demonstrate efficacy of nucleoside analogues with high antiviral activity in the treatment of such patients and importance of well-timed prescription of antiviral therapy.Key points. Presented case shows renal onset of chronic viral hepatitis B, that was previously asymptomatic for long time in patient, who was infected at early childhood. Clinical manifestation of disease was characterized by nephrotic syndrome, hematuria, systemic hypertension. Severe dependent edema, abdominal and pleural effusions, splenomegaly and hypertension up to 160/90 mm Hg drew attention. Laboratory tests revealed markers of НВе-negative НВV-infection, high serum level of НВV DNA replication, severe proteinuria at preserved renal function. At ultrasound liver elastometry showed severe fibrosis (METAVIR F3). On a background of glucocorticosteroid treatment elevation of cytolytic enzymes (alanine transaminase of 120 U/L, aspartate aminotransferase of 98 U/L) was registered for the first time. Treatment included entecavir 0,5 mg per day for 12 wks with normalization of transaminase levels, virologic response (DNA НВV under 50 МЕ/ML) at the 30th week, НВе seroconversion at the 42nd week of treatment.Conclusions. Extrahepatic manifestations of viral hepatites frequently not only mask liver disease, but determine prognosis in many respects as well. Pathogenic treatment of НВV-infection associated CGN without antiviral treatment is accompanied by risk of liver disease activation. Patients with renal involvement within the framework of chronic НВV-infection require antiviral therapy by nucleoside analogues, their high antiviral activity is demonstrated by presented clinical case.